Prevalência e classificação de canais mésio-mediais de molares mandibulares através de exames tomográficos Cone-beam - Marchiori , Vinicius (2022)
Knowledge of dental anatomy is essential for a need for successful endodontic therapy. Each dental group has the most commonly encountered anatomical characteristics, and may also present less frequent variations, but of equal importance, since the entire root canal system must be cleaned, disinfected and sealed in the best possible way. The use of Cone-Beam Cone-Beam Computed Tomography (CBCT) has great relevance for planning cases such as the presence of mesiomedial canals (MMC) in the mesial root of mandibular molars. This study aims to evaluate and classify (according to Vertucci et al., Sert & Bayirli and Ahmed et al.) the prevalence of MMC in a population of 293 individuals in western Paraná, through the evaluation of threedimensional images obtained by tomography computerized Cone-Beam from an image center in the city of Cascavel – Paraná. For this, 1198 CT scans were analyzed between August 2016 and December 2021, and 183 CT scans with dental elements that met the inclusion criteria of the work were selected, totaling 293 lower molars, descriptive statistical analysis was performed. The results obtained emphasize the low presence of MMC in the mesial roots of lower molars, the study showed a prevalence of 3.07%. The findings of this study corroborate data from the literature, with the presence of MMC being of low prevalence. However, knowledge and, especially, diagnostic resources, such as cone beam tomography, and magnification for its clinical identification, such as magnifying glasses and microscopes, are essential for a successful endodontic therapy.